2019
DOI: 10.3390/nano9121699
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal and Recovery of Metal Ions and Dyes from Wastewater through Montmorillonite Clay Mineral

Abstract: The main objective of this work was to evaluate the potential of Montmorillonite nanoclay (Mt), readily and inexpensively available, for the simultaneous adsorption (and removal) of two classes of pollutants: metal ions and dyes. The attention was focused on two “model” pollutants: Ce(III) and crystal violet (CV). The choice is due to the fact that they are widespread in wastewaters of various origins. These characteristics, together with their effect on human health, make them ideal for studies on water remed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 124 publications
2
20
0
Order By: Relevance
“…Therefore, wastewaters containing this type of dyes were highlighted as one of the most important threatening factors in environmental and public health [2,5]. Different studies have reported that there are several methods for removing dyes from textile wastewaters, including the application of photodecomposition [6], electrolysis [7,8], adsorption [9][10][11][12][13][14][15][16][17][18], oxidation [19], biodegradation [20], combined sonochemical and adsorption [21], coagulation-flocculation [22,23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, wastewaters containing this type of dyes were highlighted as one of the most important threatening factors in environmental and public health [2,5]. Different studies have reported that there are several methods for removing dyes from textile wastewaters, including the application of photodecomposition [6], electrolysis [7,8], adsorption [9][10][11][12][13][14][15][16][17][18], oxidation [19], biodegradation [20], combined sonochemical and adsorption [21], coagulation-flocculation [22,23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon-based nanomaterials such as activated carbon, carbon nanotubes (CNTs), montmorillonite and graphene may be successfully used as efficient, cost-effective and environmentally friendly adsorbents with excellent adsorption capacity for the removal of various toxic substrates from wastewater such as heavy metals, azo dyes, etc. [13]. For example, CNTimpregnated chitosan hydrogel beads have been developed for the removal of congo red with high maximum adsorption capacity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Various soils [13], montmorillonite nanoclay [14], HKUST-1 framework [15] and chert rocks [16] were used as sorbents for Ce(III) from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%